Karakteristik Teh Herbal Daun Kelor (Moringa oleifera) dengan Pengkayaan Kolagen Ikan - Wicaksono, Luqman Agung; Djajati, Sri; Laksmi, Arina Nur Evita (Program Studi Teknologi Pangan, 2020)
Herbal tea is one of the types of drinks that is in demand by the public because herbal tea is one of the functional food types that has many benefits. In addition, herbal teas are also made from natural ingredients so that it is safe and easy to consume. Herbal tea is a term for beverage products made from ingredients other than tea leaves (Camellia sinensis). Therefore, there are many natural ingredients in the surrounding environment that can potentially be processed into herbal tea products. One of them is by utilizing moringa leaves, cinnamon, roselle and secang that known for it beneficial health effect.To increase the benefits for health also added fish collagen that can support the antioxidant and protein content in this moringa leaf herbal tea product. The purpose of this study is to find out which additional ingredients have the highest antioxidant activity and are best suited to support the content in moringa leaf herbal tea and to know the best concentration of fish collagen added.From the results of the study obtained the formulation of herbal tea drinks moringa leaves which is the best treatment in this study is the formulation of moringa: cinnamon (75:25) as well as the addition of fish collagen by 3% with a total phenol yield of 10.52 mgTAE/g; antioxidant activity of DPPH method 92.16%; antioxidant activity method FRAP 9,92 mgAAE/g; total dissolved protein 16.32%, taste value 1.95 and calcium content 94.29 ppm.